Maternal and Neonatal Outcome after Caesarean and Vaginal Delivery in Eclampsia (TAJ: Journal of Teachers Association, 2018)
This randomized control trial study was conducted at Rajshahi Medical College and Hospital, Bangladesh. This study includes 70 consecutive antepartum eclamptic patients who were admitted in the year 2008. The purpose of this study was to analyze the difference in maternal and perinatal outcome in caesarean and vaginal delivery and thereby describe the success rate of a particular mode of delivery in those cases. Bivariate and multivariable regression analyses were used to determine factors that were associated with assignment to, success of, and odds of maternal and neonatal outcome after caesarean and vaginal delivery.TAJ 2011; 24(2): 111-117